2005
DOI: 10.1038/labinvest.3700210
|View full text |Cite
|
Sign up to set email alerts
|

Splenic transposition is superior to caudal shunt as a model of murine total hepatic ischemia

Abstract: Murine total hepatic ischemia (THI) followed by reperfusion without shunting of the portal vein induces significant lethality in rodents due to intestinal congestion. Two methods have been promulgated to study THI and reperfusion in mice without intestinal congestion: subcutaneous splenic transposition which creates a portosystemic shunt via epigastric vessels, and a caudal shunt with 30% hepatectomy, which creates a portosystemic shunt via the small remnant of remaining caudal lobe. We compared outcome, infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…A vasoconstrictive response of the liver remnant due to ischemia/reperfusion injury may have also been a factor in the development of portal hypertension [31,40]. In our experiments, the pathology findings of portal space and sinusoidal congestion, as well as hepatocyte swelling are also consistent with portal hypertension.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A vasoconstrictive response of the liver remnant due to ischemia/reperfusion injury may have also been a factor in the development of portal hypertension [31,40]. In our experiments, the pathology findings of portal space and sinusoidal congestion, as well as hepatocyte swelling are also consistent with portal hypertension.…”
Section: Discussionsupporting
confidence: 81%
“…It is well known that the human liver can safely withstand warm ischemia for 45-60 min without portosystemic shunt [24][25][26][27]. .In contrast, rodents and pigs can poorly tolerate even short periods of total hepatic ischemia [28][29][30][31][32][33][34]. It has been shown that 50% of rats with 45-min warm ischemia of the liver died within 7 d and no rat survived after completely blocking the hepatic artery and portal vein for 60 min [24].…”
Section: Discussionmentioning
confidence: 97%
“…The spleen was pulled out and buried in subcutaneous pouch. 12 This surgical procedure prevents portal congestion caused by PTO and enabled animals to survive. Three weeks after SST, portal trunk was ligated with 5-0 nylon sutures.…”
Section: Methodsmentioning
confidence: 99%
“…The portal clamping time in the recipient was defined as the period from the positioning of the portal clamp before removing the recipient's liver, to its removal after the completion of the suprahepatic and portal anastomoses. It is linked to animal survival because rodents are particularly sensitive to the metabolic effects caused by splanchnic congestion . The portal clamping time was constantly within 15 minutes, with a median at 12.5 ± 2.0 minutes (mean, 12.2 minutes).…”
Section: Resultsmentioning
confidence: 99%